2012
DOI: 10.1097/nmd.0b013e31825bfad9
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Problems and Cognitive Characteristics of Interpersonal Representations in Alexithymia

Abstract: In this study associations between alexithymia, interpersonal problems and cognitivestructural aspects of internal interpersonal representations were examined. Alexithymia was measured using the Structured Interview for Alexithymia (TSIA) and the Toronto Alexithymia Scale (TAS-20). To measure interpersonal problems, dominance and affiliation dimensions scores of the Inventory of Interpersonal Problems (IIP-64) were used and cognitive-structural characteristics of interpersonal representations were measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…It may be a significant clinical index that could influence family relationships. 58 Subsequent studies could explore the value of this index as a discriminant factor in relation to the kind of family functioning, the potential therapeutic alliance with the families, and perhaps the daughter’s outcome. In fact, literature considers family relationships to be more relevant than the parents’ individual personality and psychopathological traits in predicting the anorexic daughter’s alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…It may be a significant clinical index that could influence family relationships. 58 Subsequent studies could explore the value of this index as a discriminant factor in relation to the kind of family functioning, the potential therapeutic alliance with the families, and perhaps the daughter’s outcome. In fact, literature considers family relationships to be more relevant than the parents’ individual personality and psychopathological traits in predicting the anorexic daughter’s alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring metacognitive impairment that has been most extensively studied is alexithymia (Bagby, Parker, & Taylor, 1994). Alexithymia has been linked both with interpersonal problems (Nicolò et al, 2011), and with a cold, distant, and nonassertive personality style (Inslegers et al, 2012;Spitzer, Sieble-Jürges, Barnow, Grabe, & Freyberger, 2005). Positive correlations have been found with schizotypal, avoidant, and dependent personality traits (Bach, de Zwaan, Ackard, Nutzinger, & Mitchell, 1994), with schizoid and antisocial traits (De Rick & Vanhule, 2007), with Cluster C traits (Honkalampi, Hintikka, Antikainen, Lehtonen, & Viinamaki, 2001), and with avoidant, dependent, passive-aggressive and depressive traits, but not with Cluster B traits (Nicolò et al, 2011).…”
Section: Monitoring In Self-domainmentioning
confidence: 99%
“…Adopting a methodology similar to that used in Hopwood et al's study, we expect to discriminate similar personality styles with specific metacognitive impairments. We expect low monitoring performance to be related to Withdrawal, because difficulties in monitoring inner states have been found in AVPD and alexithymia has been associated with a cold and detached style (Inslegers at al., 2012). We expect decentering impairment to be associated with Peculiarity personality style.…”
Section: Current Studymentioning
confidence: 99%
“…Similar to our results, Chen et al (19) stated that patients with adjustment disorder had problems with identification of emotions, which is a feature of alexithymia. The literature has shown that individuals who display alexithymic features have a hard time identi-fying emotions, have trouble connecting with other people, and have a limited capacity for empathy, all of which combine to give them a hard time in interpersonal relationships (22,30). Alexithymic features may play a role in the manifestation of adjustment disorder symptoms or in the severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%